2020
DOI: 10.19163/2307-9266-2019-7-6-279-290
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical study of <i>Tribulus Terrestris</i> L.

Abstract: Tríbulus terrestris L., an annual herb belonging to the Zygophyllaceae family and growing in moderate and tropical climates, has a rich chemical composition of biologically active substances and chemical elements.The aim of the work is a phytochemical study of Tribulus terrestris L. growing in different geographical zones.Materials and methods. The objects of study were herb specimens of Tribulus terrestris L. collected in different habitats. The samples of the raw materials were shade-dried. The determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…Our results are consistent with those of Affaf et al, 2019 [ 49 ]. It has been established that potassium and calcium accumulate in the highest amounts among the macroelements in T. terrestris grass samples; they account for about 90% of the total content of elements in the plant.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are consistent with those of Affaf et al, 2019 [ 49 ]. It has been established that potassium and calcium accumulate in the highest amounts among the macroelements in T. terrestris grass samples; they account for about 90% of the total content of elements in the plant.…”
Section: Discussionsupporting
confidence: 94%
“…The study of the elemental composition of the creeping grass, T. terrestris, showed that the habitats (geographical zones), in which the studied samples of raw materials were collected, affect the accumulation of elements by the plant. This confirmed the position given in other works [ 9 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…Tribulus terrestris infusions, decoctions are widely used in alternative medicine in many countries. Bulgaria -erectile dysfunction treatment, Iran as a diuretic, laxative and syphilis treatment, India -radiculitis, in traditional Chinese medicine -eye diseases treatment [1]. In science-based medicine Tribulus terrestris extract is used as a booster for reproductive system.…”
Section: Introductionmentioning
confidence: 99%